2009
DOI: 10.1159/000233258
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of a Simple Adaptor Protein PDZK1: Ligand Identification, Interaction and Functional Prediction of Complex

Abstract: PDZK1 is a simple adaptor protein with four protein interaction PDZ domains, but without any other known functional domains. Here, we used yeast two-hybrid screening of a random peptide library and high-throughput validation screening of a specialized PDZ ligand candidate library to systematically and comprehensively identify PDZK1 ligands. The potential functional associations of the ligands were predicted by functional annotations from a MILANO literature search and subcellular localizations. The ligands wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Our results do not unequivocally demonstrate a direct interaction between PDZK1 and Cdc37, and it is possible that PDZK1 interacts with any member of the HSP90 complex, including HSP90 itself, Akt or any other protein that might interact with the complex. This result is likely considering the report by Hu et al (31), where a yeast two-hybrid screen of a random peptide library identified a number of putative proteins that may interact with PDZK1; however, Akt, Her2/Neu and EGFR were not among the candidates. Interestingly, other factors known to be involved in cell proliferation and signaling in breast cancer were identified in their screen, such as cyclin-dependent kinase 4 (CDK4) and insulin-like growth factor-binding protein 5 (IGFBP5) (32,33).…”
Section: Discussionmentioning
confidence: 87%
“…Our results do not unequivocally demonstrate a direct interaction between PDZK1 and Cdc37, and it is possible that PDZK1 interacts with any member of the HSP90 complex, including HSP90 itself, Akt or any other protein that might interact with the complex. This result is likely considering the report by Hu et al (31), where a yeast two-hybrid screen of a random peptide library identified a number of putative proteins that may interact with PDZK1; however, Akt, Her2/Neu and EGFR were not among the candidates. Interestingly, other factors known to be involved in cell proliferation and signaling in breast cancer were identified in their screen, such as cyclin-dependent kinase 4 (CDK4) and insulin-like growth factor-binding protein 5 (IGFBP5) (32,33).…”
Section: Discussionmentioning
confidence: 87%
“…Herein we report the identification of the intracellular adapter protein PDZK1 as a direct interactant of the hIP. Using the hIP 299–386 as the initial bait protein, Y2H screening identified several independent clones that encode amino acids 1–154 of PDZK1 (PDZK1 1–154 ), encompassing its entire PDZ domain 1 (PDZ D1 ) and part of its PDZ D2 (Hu et al , 2009; LaLonde and Bretscher, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…PDZK1 is a multi-PDZ domain adapter or scaffold protein containing four well-defined PDZ domains, hereafter referred to as PDZ D1 , PDZ D2 , PDZ D3 , and PDZ D4 , in addition to a short regulatory domain at its C terminus (Hu et al , 2009; LaLonde and Bretscher, 2009). Although the initial Y2H screen identified PDZK1 1–154 , corresponding to its entire PDZ D1 and only part of its PDZ D2 , as the region that interacts with the hIP, it was sought to investigate the specificity of the interaction of PDZ D1 and to establish whether any of the other PDZ domains, namely PDZ D2 , PDZ D3 , and PDZ D4 , may also contribute to the interaction with the hIP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular scaffold or adapter protein PDZ domaincontaining protein 1 (PDZK1) is a member of the Na + , H + exchanger regulatory family (NHERF) and is predominantly expressed in the brush border of the kidney and small intestine, in epithelial and endothelial cells, in macrophages and in the liver [111][112][113] . PDZK1 contains 4 PDZ domains, facilitating its binding to highly specific interacting partners [114][115][116] . Most notably, in the context of the CV system, through its interaction with the high density lipoprotein (HDL) scavenger receptor class B, type 1 (SR-B1), PDZK1 is essential for both reverse cholesterol transport (RCT) and for HDL-mediated vascular reendothelialization 112,117 .…”
Section: Interaction Of the Ip With Pdzk1mentioning
confidence: 99%